CEO Characteristics and Firm Financing Decision - Elsa Nur Rizky Fayzaty; Rini Setyo Witiastuti (Management Analysis Journal, 2024)
The study aims find empirical evidence of the effect of education, tenure, age, and gender of CEO on capital structure. The research is a quanitative study using secondary data sources. The population in this study were property and real estate companies listed on the Indonesia Stock Exchange in 2015-2022. The sampling technique is using purposive sampling method which obtained 34 companies, resulting in 272 observation data. The analysis method used is multiple linear regression analysis. The analysis method used is ANCOVA test analysis (covariance test). The results showed that CEO characteristics did not have a significant effect on capital structure.